Analysis of Profile and Motivation of Women's Workforce in SME Culinary Sector - Dinda Syakinah (Institute of Computer Science (IOCS), 2020)
Small and Medium Enterprises (SMEs) can be viewed as a rescue valve and recovery process as well as national economic development especially since the monetary crisis in 1998. The success of SMEs in Indonesia in it can not be separated by the important role of women who can improve the country's economy. Most SMEs are concentrated in the production and service sectors, one of which is the culinary sector that requires a lot of female workers, both for married and unmarried women (teenagers) and does not require high education with them. Work only with cooking skills. This research was conducted in Small and Medium Business Culinary in Kecamatan Medan Selayang. This study aims to find out and analyze how the profiles and factors that motivate female workers to work in the small business sector of culinary (studies in SME Kecamatan Medan Selayang). The method used in this research is descriptive qualitative method with indepth interview. Data collection techniques used were interviews and observation. The researcher chooses to determine the informant by using accidental sampling technique in which the sampling method by choosing who happens to be or found by the researcher. Based on the results of the analysis, the factors of female worker motivation in the Small and Medium Businesses in Medan Selayang District are due to the economic need or the desire to live decent, education level, leisure time, hobbies and skills, environment and financial flexibility. The profile of female workers in Small and Medium Enterprises of Culinary in Medan Sub-district, in terms of the average age of female workers aged 21 years up to 55 years, in terms of education the informants have different levels of education starting from elementary to graduate. When viewed in terms of marital status found 3 different types of status that is married and have children, not married, and have no husband (divorce live/death).